Impact of tighter regulations on performance of hedge funds in South Africa: a case study of selected industry stakeholders - Manzini, Richard (My University, 2019)
Introduction and Background: Historically, hedge funds in South Africa as noted by Betsalel (2006) have been largely an unregulated investment vehicle that accumulated billions of rands in assets under management. In 2015 South Africa became the first country to introduce comprehensive regulation for hedge fund products. The new regulations provide for two categories of hedge funds, namely Qualified Investor Hedge Funds and Retail Investor Hedge Funds. This required the hedge fund industry to prioritise the conversion of hedge fund products to structures that conform to the provisions of the Collective Investment Schemes Control Act (CISCA). Aim and Objectives: This study examines Hedge Fund stakeholders’ views on the effects that the transition to regulated environment has on the Hedge Fund Industry, first understand the effect of regulations on hedge funds post-promulgation of the new regulations in 2015, and second, to identify the challenges posed by these regulations. Methods: To investigate the research aim, the research employed a cross-sectional two-fold mixed-methods approach which was a mixed methodological approach including qualitative and quantitative components. The qualitative component of this study involved in-depth key-informant interviews while the quantitative component utilised a semi-structured, electronically distributed self-administered questionnaire. The quantitative component was included in order to further investigate the qualitative themes obtained from the qualitative component. Results: The results indicate that the SA financial services is comprehensively regulated. Since promulgation of the CISCA Act, HFs have been adhering to governance and all regulations that pertain to them. In terms of transitioning, by end of 2017, more than 65% of HF assets had moved to Qualified Investor Hedge Funds and 24% to Retail Investor Hedge Funds. The majority of respondents agreed that the Hedge Fund Industry is important to the South African Financial Services Market because among others, the industry has an important social role and provides value to the broader economy, beyond facilitating market efficiency. Conclusion: Regulated hedge funds tend to reduce the chances of things going wrong for hedge fund investors and thus enhance the reputation of hedge funds and dispel some of investors’ doubts. There is the general feeling that enhanced disclosure and risk control measures supports better protection but could mean higher admin costs. The enhanced disclosure ensures that investors know what they are getting into and present an opportunity to hold fund manager accountable through appropriate legal provision. Overall, regulation supports the better management of systemic risk that can have ramifications for the financial system.
This Research Report is submitted in fulfilment of the requirements for the degree of Master of Management in Finance & Investment in the Faculty of Commerce Law and Management at the University Of The Witwatersrand Business School, March 2018
Keywords: Hedge funds; Hedging (Finance); Investment banking